Basic Orthodontic Knowledge for General Practitioners - Chaukse, Ankur; Jain, Sandhya; Dubey, Rachna; Chaukse, Nishta; Kawadkar, Abhishek; Jain, Gauravi (Journal of Orofacial Research, 2012)
Awareness of malocclusion and the need for correction for esthetics and confidence is increasing nowadays in population. Patients with malocclusion have no specific signs and symptoms, but may complain about esthetics, maintenance with hygiene and mastication. Thus, pleasing smile is often the major factor whichmotivates patients to seek orthodontic treatment. Most of the times orthodontic treatment is carried in early permanent dentition, typically at 12 ± 13 years old when the second molars erupt. However, it is important to make an annual assessment in the mixed dentition to identify developing problems and arrangetreatment. One of the most harmful misconceptions in dentistry is that orthodontic treatment cannot be started before permanent teeth are fully erupted. Orthodontic screening can be done at any age. The American Association of Orthodontists (AAO) also recommends that every child should be seen by an orthodontist at the first signs of orthodontic problems or no later than age 7. Therefore, it is very important to get basic idea about orthodontic treatment and the time when it is required. This paper describes about orthodontic treatment timing, clinical examination of patient, uses of removable appliances and orthodontic case considerations.